PENDAMPINGAN BURUH MIGRAN OLEH RADIO KOMUNITAS CARAKA FM Studi Kasus Radio Komunitas Caraka FM Desa Ciborelang Kecamatan Jatiwangi Kabupaten Majalengka - Aripin Ipin (ORASI: Jurnal Dakwah dan Komunikasi, 2016)
Aripin. NIM: 14113541280, "Assistance Migrant Workers by CARAKA FM Community Radio (A Case Study of Rural Community Radio FM CARAKA Ciborelang Jatiwangi District of Majalengka)"        Empowerment is done in the form of education about the importance of knowing the requirements to become migrant workers, forms of trafficking and about the importance of not falling back. Slightly sekalli parties try to deal with the victims with the efforts of more fundamental and sustainable. Therefore, it would need dicarai a model of empowering trafficking victims were able to resolve the fundamental problems of both aspects of the reception of clear information such as the introduction of the contents of human trafficking, the analysis of human trafficking cases, dialogue with the victims, and also makes the role of institutions, especially institutions of religious education in the prevention of trafficking manuisa in an effort to resolve the fundamental problems of trafficking victims both from the aspect or aspects of healing trauma debriefing to continue a better life in the future.        From the results of mentoring migrant workers victims of trafficking carried out by radio komuitas emissary fm has an impact on society and especially to former migrant workers, they understand the process of a migrant worker is legal, their sisters about the difference workers leaving legally and illegally (trafficking), knowing the rights of migrant workers and has the power to liberate themselves in the confinement of people who are not responsible. In addition to the general public become more open about their experiences and they are more sensitive to the environment in the village Ciborelang and care for each other. Keywords: Community Radio, Assistance, Migrant Workers